The relationship of computer attitudes to reported use and observed behavioral proficiency. - Barcy WR; Barcy RT (Journal of Technology in Human Services, 2008)
The current health care delivery system increasingly relies upon information technology (IT) to more effectively and efficiently meet patient needs. This paper reports findings from an observational field study that examined the relationship of computer self-efficacy, computer anxiety, and perceived computer usefulness to behavioral performance utilizing IT programs by clinical staff in a hospital-based social work and nursing case management department. The results indicated significant relationships between observed behavioral proficiency on a computer resource directory search task and self-reported ratings of computer selfefficacy and computer anxiety. Higher task proficiency was associated with higher computer self-efficacy ratings. Lower task proficiency was associated with higher computer anxiety. More frequent self-reported use of the computer resource directory was significantly associated with higher ratings of computer usefulness.